Skinfold thicknesses and leg-to-leg bioimpedance for the assessment of body composition in children - COCETTI, Monize (2009)
ObjectiveThe objective of this study was to compare the components of body composition obtained by leg-to-leg bioimpedance and skinfold thickness measurements in children. MethodsTriceps and subscapular skinfold thicknesses and TANITA TBF-300A leg-to-leg bioimpedance were used to determine the body composition of 1.286 schoolchildren (703 girls and 583 boys) aged 7 to 9 years. The Pearson’s correlation coefficient (r) and Bland-Altman plot were used to analyze the agreement between the two methods. ResultsThe two methods correlated strongly and significantly for girls´ and boys´ percentage of body fat (0.77 and 0.89, respectively), fat mass (0.93 and 0.94 respectively) and lean mass (0.92 and 0.89 respectively). The BlandAltman plot also showed good agreement between the methods, since only a few points corresponding to the differences between the measurements obtained by the two methods were outside the confidence interval. ConclusionThese results show that both methods, triceps and subscapular skinfold thicknesses and leg-to-leg bioimpedance, can be used to asses the body composition of schoolchildren in population-based studies. Yet, the wide variability observed in some measurements suggests that either method should always be associated with other indicators to assess body composition.